Analisis pertandingan liga 2 “deltras vs persela lamongan” terhadap perekonomian di kabupaten Sidoarjo - Windi Asri Ila Firda; Dwiki Mardiyanto (Jurnal Riset Pendidikan Ekonomi, 2023)
Football as one of the entertainment activities that has a lot of fanaticism fans. This fanaticism has a positive impact, for example, by helping to increase sales from football club activities. Football clubs are also designated as taxpayers and have an obligation to pay taxes if their income is above IDR 4.8 billion a year. The results of this tax revenue can later be used by local governments to carry out development to increase the economic tarag of a region. This study aims to determine whether the League 2 match “Deltras Vs Persela Lamongan” has an effect on the economy in Sidoarjo Regency. The type of research used is descriptive qualitative research. The data used comes from secondary sources with the method used is the study of documentation. Data processing uses qualitative techniques. The results showed that the League 2 match “Deltras Vs Persela Lamongan” had an indirect influence on the economy of Sidoarjo. It is said like that because the role of the football club is to pay taxes to the regions which will later be used for economic development to facilitate community economic activities,